The Influence of Lifestyle and Trust in the Use of Shopee Paylater Services on Consumer Behavior in the Maqashid Sharia Perspective (Study on Students of UIN Raden Intan Lampung) - Is Susanto; Moh. Mukri; Moh. Bahrudin; Faisal Faisal (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to investigate the influence of lifestyle and trust in the use of Shopee Paylater services on consumer behavior, taking into account the Maqashid Sharia perspective, especially for students of the Faculty of Economics and Islamic Business at UIN Raden Intan Lampung. This research adopts a quantitative approach through the survey method and the use of questionnaires as a data collection technique. The research sample consisted of 84 students from the class of 2021 who used the Shopee Paylater service, selected through purposive sampling. The data were analyzed using multiple linear regression with the help of SPSS software. The independent variables used in this study include lifestyle (X1) and trust (X2), while consumer behavior (Y) is the dependent variable. The t-test results indicate that both lifestyle and trust individually have a positive and significant influence on consumer behavior. The F test results indicate that lifestyle and trust together have a positive and significant effect on consumer behavior. In the context of Maqashid Sharia, consumption that is carried out not only follows religious teachings, but also provides tangible benefits for individuals and society as a whole.